Knowledge Attitudes and Practices (KAP) of Hand Washing among Selected School Children of Dhaka City (Ibrahim Cardiac Medical Journal, 2024)
Background & objective: Communicable diseases like diarrhoea and acute respiratory tract infection are the commonest cause of morbidity and mortality in children of developing countries. Children are more vulnerable to food and water-borne diseases. Hand washing is an effective method for preventing communicable diseases particularly water-borne diseases. The purpose of this study is, therefore to evaluate the knowledge, attitudes, and practices (KAP) of hand washing among selected primary-level school children of Dhaka City as a mode of disease prevention.Methods: From January 1st to June 30th, 2016, primary school students (only those in the fifth grade) in Dhaka City participated in this descriptive, cross-sectional survey. Following ethical approval from the school authority, the local guardian of the children, a total of 252 children were purposively enrolled from various elementary schools in Dhaka City. The knowledge of hand washing included in this study comprises information on cleaning hands before meals, after urinating, defecating, and playing, procedures for washing hands, information about World Hand Washing Day, instructions for washing hands, facilities for washing hands, and materials for washing hands. We offered each respondent ten questions, with a mark of 1 for each accurate response, to gauge their degree of expertise.Results: Over 70% of the respondents were 11-12 years old with the mean age of the respondents being 10.8 ± 0.7 years. The boy-to-girl ratio was roughly 11:9. While respondents’ fathers were primarily service-holder (about 55%) mothers were generally housewives (70%). Sixty percent of the respondents had 3-4 members in their family. The majority (98%) of the respondents knew about hand-washing. However, over two-fifth (42.2%) of them were completely unaware of the steps of hand-washing, and nearly 70% did not know the minimum hand-washing time to wash out the bacteria attached to the hand surface. Overall, 55.2% of the respondents had good knowledge, 32.5% had adequate knowledge, and 12.3% had excellent knowledge about hand-washing.Conclusion: The study concluded that most of the students usually wash their hands in critical times; however, they do not know the correct way and steps of hand washing. So, more attention is to be paid to training children to adopt healthy hand-washing behavior. The importance of hand washing should be included in their regular curriculum.Ibrahim Card Med J 2023; 13 (1&2): 66-70